Obesity in people living with mental health disorders: Scoping review of strategies to recognize, prevent, and manage - Opusunju, Ellis (2018)
Objective: To identify and synthesize evidence regarding obesity prevention and management strategies for the control of the weight of people living with mental health disorders (PLMDs) who are in pharmacological treatment. Materials and Methods: Design: Scoping review. Data sources: Searches in the CINAHL, Medline, PubMed, Ovid and ProQuest databases. Method of revision: Database search with the key words: obesity, psychiatry, mental health, intervention, management, medication and obesity. Studies identified with a five-year publication limit, published in English or Spanish that would have abstracts in English. The project resulting in this scoping review was approved by the university institutional review board. Results: 60 articles were identified that address the prevention and management of obesity in PLMDs. Three thematic areas were recognized when considering all articles: 1) people with mental disorders and obesity, 2) knowledge and attitudes of physicians on the treatment of obesity and 3) preventive interventions for people with mental disorders. PLMDs has a high risk of developing obesity and related pathologies like cardiovascular diseases. Factors such as poor diet, low physical activity, consumption of psychotropic drugs and social vulnerability may be the causes. Mental health professionals are focused on the treatment of mental disorders, leaving aside issues related to obesity, approach for which there are not feeling to have enough trained, although existence of successful experiences on weight reduction interventions in the literature. Conclusions: The training of mental health professionals should include strategies to address obesity in PLMDs. There needs to be increased resources dedicated to developing educational programs for mental health professionals and disseminating evidence-based clinical practice guidelines focused on the management of obesity in this high-risk group.